Performance in Multi-Joint Force-Plate Assessments in Male and Female CrossFit® Athletes - James R. Jowsey; G. Gregory Haff; Paul Comfort; Nicholas Joel Ripley (Biomechanics)
Background: CrossFit® aims to be equitable between both males and female athletes, supporting equal representation and equal prize money at international events. However, to date, limited information is known on CrossFit® athletes’ performance in the countermovement jump (CMJ), countermovement rebound jump (CMR-J), and isometric mid-thigh pull (IMTP) when assessed using force plates, and if there are any differences between sexes. Therefore, the purpose of the present study was to observe whether any sex-based differences and relationships exist between performance within these assessments. Methods: A total of CrossFit athletes (43 male = 32.8 ± 9.0 years; height 1.78 ± 0.06 m; mass = 92.4 ± 10.6 kg; and 31 female = 31.0 ± 7.6 years, height = 1.64 ± 0.05 m; mass = 68.8 ± 6.0 kg) completed three trials of CMJ, CMR-J and IMTP using portable dual-system force-plate sampling at 1000 Hz. Results: Moderate–large relationships were observed between CMJ, CMR-J and IMTP outcome measures (r = 0.396–0.809, p < 0.001). Males demonstrated small to moderately greater performance outcomes than females for CMJ height (males = 0.35 ± 0.08 m; females 0.30 ± 0.06 m, d = 0.73), CMR-J height (males = 0.32 ± 0.08 m; females = 0.30 ± 0.06 m, d = 0.39) and IMTP peak net force (males = 30.62 ± 10.01 N·kg−1; females = 27.49 ± 6.44 N·kg−1, d = 0.29). Conclusions: Maximal relative strength in CrossFit® athletes should be seen as imperative in both male and female athletes due to the meaningful relationship in ballistic and plyometric ability. Moreover, previous relationships with CrossFit® performance and the injury risk reduction benefits of improving strength provide further support. The descriptive data presented could be used by CrossFit® coaches to assess and compare the current performance of their own athletes in a battery of tests examining CMJ, CMR-J and IMTP, while also facilitating decisions upon prescription within training and competition.